Manajemen Catering yang Efektif guna Meningkatkan Produktivitas - Ambarwati, Mitra Mila; Nurkhasanah, Tri Ayu; Meilani, Ucik Putri; Qolbi, Latifatul; Al-Dillah, Azzara; Sari, Windah; Imama, Dhea Safina; Adilia, Sabila Putri; Putri, Oktaria Ardika (Welfare : Jurnal Pengabdian Masyarakat, 2025)
The research was motivated by several challenges faced by Kenz Catering in the form of lack of use of digital marketing media, lack of coordination and communication, consumer demands who want high quality products at affordable prices, and the many competitors who are more innovative. The aim of this research is to implement effective catering management to increase productivity at Kenz Catering. The method used in this research is Participatory Action Research (PAR) using observation, interviews and acting in the field. Carrying out activities in the form of an internship for several days and looking for solutions to the problems faced by Kenz Catering. To optimize marketing management, Kenz Catering is trying to increase promotions through digital media.